Phytocontact Dermatitis due to Mustard Seed Mimicking Burn Injury: Report of a Case - Hakan Yabanoglu; Sami Akbulut; Feza Karakayali (Case Reports in Medicine)
Mustard seeds have been used in traditional folk medicine as a stimulant, diuretic, and purgative and to treat a variety of ailments including peritonitis and neuralgia. Mustards are still used today in mustard plasters to treat rheumatism, arthritis, chest congestion, aching back, and sore muscles. To make a mustard plaster, mix equal parts of flour and powdered mustard and spread it as a paste on a doubled piece of soft cloth. Apply mustard plaster to the affected area for a maximum of 15 minutes. Prolonged application can result in burns to the skin and nerve damage. Skin lesions occur within hours after exposure, and there is no significant therapy procedure. This case report is about a patient with second-degree burn, occurred when a mixture including mustard seed was exposed to her skin in the pain therapy of the osteoarthritis in her left knee. There are no studies analyzing treatment of skin burns induced by mustard seed in the literature. While in this type of burns our experience is limited, we think that conservative approach should be first choice of treatment.